Penguatan Data Kepariwisataan di Desa Lembar Selatan untuk Mengungkap Potensi Desa menuju Dewi Cantik: Penguatan Data Kepariwisataan di Desa Lembar Selatan untuk Mengungkap Potensi Desa menuju Dewi Cantik - Hidayati, Lilik; Mustika Hadijati; Desy Komalasari; Nur Asmita Purnamasari; Adis Tia Juli Agil Asri; Kamal Faisal Hikam (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
South Lembar Village has very promising tourism potential, both in terms of natural beauty, cultural richness, and unique ecotourism such as Cemare Beach, the Sacred Tomb, and the Mangrove Forest area. However, the utilization of this potential has not been optimal due to low awareness among the community and village officials regarding the importance of data in tourism management and development. Additionally, limited technical capabilities in data collection and analysis also pose an obstacle to creating effective and sustainable tourism promotion and development strategies. Based on this urgency, this service activity aims to increase community and village government awareness and capacity in building a simple, participatory, and sustainable tourism data collection system, thru the DEWI CANTIK or Desa Wisata Cinta Data Statistik concept approach. The methods used include socializing the importance of data, providing technical training for village officials and tourism awareness groups, assisting with the use of simple software for data management, forming village data working groups, and developing standard operating procedures for tourism data management. All stages are carried out collaboratively and adapted to local conditions. The targeted outcomes of this activity include increased data literacy among the community, the formation of a Village Data Working Group as tourism information managers, the development of standard operating procedures for the village tourism data collection system, and the availability of data that can be used for more targeted and evidence-based tourism planning and promotion. With this program, it is hoped that Lembar Selatan Village can become a model for independent, innovative, and sustainable data-based tourism villages.